Reproducibility of the brief religious coping inventory with African athletes’ sample using ordinal factor analytical approach - Agormedah, Edmond Kwesi; Quansah, Frank; Srem-Sai, Medina; Ankomah, Francis; Hagan, John Elvis; Schack, Thomas (Frontiers in Psychology, 2023)
Previous studies have revealed that athletes experience stress before impending competitions due to the mental preparations they go through, the uncertainty of sporting outcomes, and other organizational issues before and during competitions. Most often than not, these athletes with religious inclination, especially those in Africa, are found to adopt religious coping due to the predominant religious values. The purpose of this research was to assess the reproducibility of the brief RCOPE instrument in an African setting using athletes' samples from different countries. Methods: By employing the ordinal factor analytical approach, exploratory and confirmatory factor analyses were performed to understand the latent structure of RCOPE and as well to examine its construct validity and reliability in the African setting. Surveying athletes from 3 African countries who participated in the West African University Games, the brief religious coping instrument was administered to the athletes for validation purposes before the competition. Results: This validation study confirmed the two-factor dimension (positive and negative religious coping) of the brief religious coping measure. Further, all items for each of the dimensions of the inventory were, at least, internally consistent. The positive and negative religious coping dimensions contributed more than half of the variance of their respective indicators. Conclusions: Sufficient evidence was gathered to support the interpretation and use of the brief religious coping measure. Coaches and sports psychologists could adopt the brief RCOPE measure to understand the mental or thought patterns of religious athletes based on existential concerns or stress accrued from impending competitions to inform appropriate religious coping interventions. This notwithstanding, the Minimum Clinical Important Difference (MCID) of the brief RCOPE should be further investigated to enhance the utility of the instrument for use in intervention-based studies